Basis enrichment and solid-fluid coupling for model-reduced fluid simulation - Gerszewski, Dan; Kavan, Ladislav; Sloan, Peter-Pike; Bargteil, Adam W. (ACM, 2015)
We present several enhancements to model-reduced fluid simulation that allow improved simulation bases and two way solid-fluid coupling. Specifically, we present a basis enrichment scheme that allows us to combine data driven or artistically derived bases with more general analytic bases derived from Laplacian Eigenfunctions. We handle two-way solid-fluid coupling in a time-splitting fashion— we alternately timestep the fluid and rigid body simulators, while taking into account the effects of the fluid on the rigid bodies and vice versa. We employ the vortex panel method to handle solid-fluid coupling and use dynamic pressure to compute the effect of the fluid on rigid bodies.
Keywords: fluid simulation; model reduction; solid-fluid coupling; UMBC Computer Animation Lab